AUTOMATIC TEST GENERATION USING LARGE LANGUAGE MODELS - Damir Rakhmaev (Modern American Journals, 2025)
This article explores approaches to using LLM to generate various test types, including unit tests, integration scenarios, and specification-based tests. A comparative analysis of the advantages and limitations of this approach in the context of test automation is provided. Particular attention is paid to assessing the quality of generated tests, the interpretability of LLM decisions, and identifying promising areas for further research and the practical implementation of these technologies.
Keywords: Large language models, automated testing, code generation, unit tests, software engineering.